Hubungan Pendidikan dan Pekerjaan dengan Pernikahan Dini Pada Masa Pandemi Covid-19 di KUA Rao Pasaman Timur Sumatra Barat - Fanny Mega Sari; Syafiq Ahmad (STIKes Hang Tuah Pekanbaru, 2021)
According to UNICEF in the next decade, there will be 10 million girls who will potentially become brides at a very young age, this number will increase by 10% for the next 10 years, in the 3 highest countries namely India, Nigeria, and Africa and including Indonesia. West Sumatra also experienced a spike and for example, Pasaman was ranked first for the incidence of early marriage, totaling 159 couples. This study employed a descriptive quantitative method with a Secondary Data Analysis (ADS) approach. The population was 760 women taken by purposive sampling and simple sampling techniques with a total of 263 women. The instrument used was the master table test, with statistical tests using the chi-square formula based on the results of the relationship between education and employment levels. It can be concluded that the following two variables have a significant relationship with the number of early marriages. The majority of women who are married in KUA Rao Pasaman have and higher education and a job, and there is a significant relationship between the degree of education and the age at the time of marriage, which is categorized as significant.